The rapidly changing Arctic - Johansson, Margareta; Callaghan, Terry; Dunn, Cameron (TSG - Top spec geography, 2010)
This book explores the Arctic, one of the last remaining wildernesses on Earth but a unique environment which is increasingly threatened. It investigates the physical systems of the Arctic region including the role of climate and ice in influencing the ecology and landforms of the high latitudes. The threat of climate change is explored in detail, drawing out the range and scale of changes that are influencing, and are likely to influence, human activity and ecosystems in the region.